Gold mineralization in the snow lakewekusko lake region, manitoba - A. G. Galley; D. V. Ziehlke; J. M. Franklin; T. M. Gordon (Canadian Institute of Mining, Metallurgy and Petroleum, 1986)
The Snow Lake-Wekusko Lake region of northern Manitoba conta ins numerous lode gold occurrences, including the largest gold deposit in the Churchill Prov ince, the Nor Acme mine. The Aphebian volcanic and sedimentary rocks of this region are comprised of submarine volcanic strata, overlain by turbidites, both of the Amisk Group, and fluvi atile sedimenta ry strata and bimodally composed subaerial volcanic rocks of the overlying Missi Group. Gold occurs as: 1) accessory gold in volcanogenic massive sulphide deposits, 2) lode gold in shear zones related to sy n- to post-FI thrust fa ults, and 3) lode-gold associated with post-F2 fault . An alteration a emblage of biotite, al bite and calc ite is associated with both groups of lode-gold deposits, and has been superimposed on the regionall y-developed metamorphic assemblages. AJthough these deposi ts are spatial ly related to britt le-ductile faul ts of different initial ages, they appear to have all fo rmed after the major period of reg ional fo lding and metamorphism, and thus may be penecontemporaneous. The alteration is different from the sericite-ankerite-quartz assemblage that is typically associated with gold deposits in Superio r Prov ince. Deposits in thi s area of Churchill Prov ince may have formed either at a higher temperature or a deeper structu ra l level than tho e in Superior Prov ince.